Organo or Metal Complex Catalyzed Synthesis of Five-membered Oxygen Heterocycles - Kaur, Navjeet; Ahlawat, Neha; Grewal, Pooja; Bhardwaj, Pranshu; Verma, Yamini (Current Organic Chemistry, 2019)
The reactions involving the formation of C-O bond using metal as a catalyst have emerged to be one of the most influential reactions for the synthesis of heterocycles in modern organic chemistry. Catalysis by metals offers diverse opportunities to invent new organic reactions with a promising range of selectivities such as chemoselectivity, regioselectivity, diastereoselectivity, and enantioselectivity. The methodologies used earlier for synthesis were less approachable to the organic chemist because of their high cost, highly specified instrumentation and inconvenient methods. For both stereoselective and regioselective formation of five-membered O-containing heterocycles, cyclic reactions that are metal and non-metal-catalyzed have known to be very efficient. The present review article covers the applications of metal and non-metal as a catalyst for the synthesis of five-membered O-containing heterocycles.
Keywords: synthesis